The Physicochemical Properties of Dendeng from Rejected Laying Hens Meat with Giving Basil Leaves - Harapin Hafid (Jurnal Peternakan Integratif, 2025)
This study aims to determine and evaluate the effect of basil leaf extract (Ocimum basilicum L) on the physicochemical properties of dendeng made from rejected laying hens meat. Rejected laying hen meat was treated with basil leaves at various concentrations, namely 0%, 10%, 15%, and 20%. The data were analyzed using analysis of variance based on a completely randomized design with 4 treatments and 4 replicates. The variables observed in the physicochemical test included tensile strength, yield, pH, and moisture content. The results showed that the addition of basil leaves to  dendeng had a significant effect (p<0.05) on the physicochemical properties of dendeng. It was concluded that basil leaves could reduce tensile strength, yield, and moisture content, and affect pH